Factors Associated with Timely Initiation of Breast Feeding among Mothers Attending Maternal and Child Health Clinic at Government Institutions of Biratnagar - Neupane, Saraswati; Dahal, Tulasha; Khadgi, Karishma (Journal of Biratnagar Nursing Campus, 2023)
Background: Timely initiation of breastfeeding (TIBF) means giving breast milk to newborn within the first hour after birth, as recommended by WHO. This is an important part of good breast feeding practices that helps to reduce infant illness and death. So, this study is conducted to identify the factors associated with TIBF among mothers having child of 9-15 months attending at government health institutions.Methods: A cross-sectional research design was used among purposively selected 206 mothers having children 9-15 months who were attending the Maternal and Child Health (MCH) clinics at Koshi Hospital and Family Planning Association of Nepal in Morang district. Data was collected through interview using a self-developed structured questionnaire. Data was analyzed using descriptive statistics, additionally factors affecting TIBF were analyzed by bivariate and multivariate logistic regression analysis.Findings: The findings reveal that among 206 mothers, less than half (49%) had initiated breast feeding within one hour of birth and more than half (56.8%) had done exclusive breastfeeding to their baby till 6 months. Mothers belonging to madhesi ethnicity (OR= 2.394, 95% CI=1.219-4.700, p- 0.011), mothers having normal delivery (OR= .461, 95% CI= 0.250- 0.851, p-0.013), multiparous (OR=1.965, 95%, CI= 1.099- 3.514, p- 0.023), lower middle economic class (OR=1.848, 95%CI=1.009-3.382, p- 0.047) were more likely TIBF than others. TIBF is significantly associated with exclusive breastfeeding (p=0.007).Conclusion: The study concludes that ethnicity, mode of delivery, parity and socio-economic status are the factors associated with TIBF. Furthermore, TIBF is connected with practice of exclusively breast feeding.